Heat Shock Proteins as Modifying Factors in Physiological Stress Responses in Poultry - Farjam, Abdoreza Soleimani (2011)
Five experiments were conducted to investigate the effects of genetic and neonatal manipulation on physiological stress response and their roles in thermotolerance parameters such as plasma corticosterone concentration (CORT), heterophil to lymphocyte ratio (HLR), heat shock protein 70 (Hsp70) and glucocorticoid receptor (GR) expression, body temperature, performance and Salmonella enteritidis resistance in poultry. In Experiment I, two trials were conducted to compare the thermotolerance of the red jungle fowl (RJF) (Gallus gallus spadiceus), village fowl (VF) and commercial broilers (CB) at (i) a common age (30 days old) and (ii) a common body weight (930±30 g) when exposed to 36 ±1 oC for 3 h. In both trials, irrespective of the stage of heat treatment the RJF had lower HLR, higher CORT concentration and higher Hsp70 expression than the VF and CB. Unlike the RJF, heat exposure significantly elevated the body temperature, HLR, CORT concentration and Hsp70 expression of CB. Experiment II was carried out to further ascertain the functional roles of CORT and Hsp70 in acquisition of thermotolerance through neonatal feed restriction. A total of 180 day-old broiler chicks were subjected to one of the following four feeding regimens: ad libitum (control); 60% feed restriction on days 4, 5 and 6 (FR60); 60% feed restriction on days 4, 5 and 6 +1500 mg/kg metyrapone (FR60M); 60% feed restriction on days 4, 5 and 6 +1500 mg/kg quercetin (FR60Q). To elicit heat stress from day 35 to 42, all chicks were exposed to 37±1°C for 3 h daily. The results suggest that subjecting chicks to FR60, as measured by HLR, FCR and weight gain, can enhance their ability to withstand, high ambient temperature and Hsp70 induction did not appear to play a profound role in the acquisition of thermotolerance. To gain more insights on the roles of Hsp70, the Hsp70 response and S. enteritidis colonization were investigated in neonatally feed restricted broiler chickens subjected to heat stress later in life in Experiment III. Chicks were divided into three feeding regimens: ad libitum (control); 60% feed restriction on days 4, 5 and 6 (FR60); 60% feed restriction on days 4, 5 and 6 +1500 mg/kg quercetin FR60Q). On d 35, all chickens were individually inoculated with 1 mL S. enteritidis (1.5×108 cfu/bird) and exposed to 37 ±1°C for 3 h daily. After heat exposure, the FR60 and FR60Q birds showed a significantly lower S. enteritidis colonization and lower Hsp70 expression than control birds. The least colonization was observed in the FR60Q group (1.38 log10 cfu/g in spleen and 1.96 log10 cfu/g in cecal content) and the highest in the control group (2.1 log10 cfu/g in spleen and 4.42 log10 cfu/g in cecal content). This clearly demonstrated that neonatally feed restricted chicks developed their thermotolerance ability and a greater ability to respond to the S. enteritidis invasion. In Experiment II we emphasised on relationship between CORT and Hsp70 responses under heat stress. To elaborate more on this relationship, Experiment IV was conducted to determine the relationship between Hsp70 expression in the heart and brain and CORT modulated by ascorbic acid and α-tocopherol supplementation in quails subjected to social isolation. Fifty three day old male Japanese quails were randomly assigned to each one of the six feeding regimens for 3 days as follows: (i)Basal diet (control); (ii) Basal diet+1500 mg/kg metyrapone (BM); (iii) Basal diet+30 mg/kg corticosterone (BCO); (iv) Basal diet +250mg/kg ascorbic acid (BC);(v) Basal diet +250mg/kg α-tocopherol (BE); (vi) Basal diet +250mg/kg ascorbic acid and 250mg/kg α-ocopherol (BCE). The birds were subsequently subjected to social isolation stress for 2 hours. Two hours of isolation stress elevated CORT significantly in the control and BE but not in the BC, BCE and BM birds. Isolation stress increased Hsp70 expression of the brain and heart in the control and BM birds. However, Hsp70 expression was not significantly altered after isolation stress by supplementation of ascorbic acid, α-tocopherol or their combination. Although CORT did not increase after isolation stress, Hsp70 expression significantly increased both in the heart and brain. Moreover, exogenous corticosterone supplementation did not result in elevation of Hsp70 expression. The last Experiment (Experiment V) was conducted to investigate the long term impact of neonatal feed restriction on the HPA axis response and hippocampal Hsp70 expression in senescent quail exposed to acute heat challenge. Equal numbers of male Japanese quails (Coturnix coturnix japonica) were subjected to one of the following two feeding regimens: ad libitum (control); 60% feed restriction on days 4,5 and 6 (FR). At the age of 21 (young) and 270 (old) days, four groups of 10 quails each from the control or FR group were randomly selected and blood and hippocampus samples were collected representing the different stages of heat treatment: Basal (no heat treatment), 1 h h at challenge (43°C), 1 h recovery and 2 h recovery. With the use of real-time PCR and EIA, the expression of regulatory genes in the hippocampus and CORT were examined. Aging resulted in a higher CORT,lower Hsp70 and GR expression in control birds, while in senescent FR birds only Hsp70 expression was attenuated following heat challenge. It is interesting to note that regardless of the age, there was a significantly lower basal GR expression in FR than control birds. Moreover, Hsp70 expression was upregulated in senescent FR birds during the recovery period and basal condition compared to control. Together, it can be concluded that selective breeding for phenotypic traits has resulted in tremendous alterations in the physiology of CB and concomitantly the ability to withstand high ambient temperature as compared to the RJF and VF. In other words, selective breeding consciously or unconsciously reduced physiological stress response thresholds in CB, producing more stress susceptible phenotypes rather than stress resistant ones. It is also apparent that genetic differences in body size and age per se may not determine breed or strain variations in response to heat stress. Neonatal modification seems to modify this stress response pattern leading to improved FCR and enhanced weight gain and resistance to S. enteritidis colonization. The Hsp70 and CORT alone are probably insufficient for inducing thermotolerance in chicks during neonatal modification and further studies are needed to investigate the participation of other genes and mechanisms during maturation of the thermoregulatory system. With regard to the relationship between Hsp70 and CORT, it is hypothesized that although Hsp70 expression may have been modulated by the effect of CORT in oxidative stress or glucocorticoid receptor association with heat shock proteins, it may also have been regulated mainly by ACTH functions in the HPA axis. It is also evident that the effect of neonatal modification on HPA axis response may last life-long. Thus, it is revealed to be a functional approach to reduce the allostatic load and restore homeostasis more efficiently in senescent birds leading to the development of adaptive, healthy and resilient phenotypes.